2019
DOI: 10.1051/matecconf/201929003016
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Fiber and CO2 Laser Cutting Accuracy

Abstract: The aim of the conducted research was to compare the functional properties and the cutting accuracy of items produced using Fiber lasers in comparison with CO2 lasers. The object of 6 mm thick sheet plates made of S235JR steel cut with the two different laser types were analyzed. The tests covered dimensional accuracy (in accordance with the PN EN 22768-fH standard) and the surface after cutting (in accordance with the PN-EN ISO 9013: 2017-04). The results of the analysis have demonstrated that for the same we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…They recommended fiber laser for continuous and mass production. In another study, performed by Robert Sołtysiak et al [22], a comparison of fiber laser and CO 2 laser was performed with respect to the functional properties and cut quality of the cut edge for 6-mm-thick S235JR steel. Characterization of the cut specimens showed high accuracy, low surface roughness value, and good repeatability for both sources.…”
Section: Introductionmentioning
confidence: 99%
“…They recommended fiber laser for continuous and mass production. In another study, performed by Robert Sołtysiak et al [22], a comparison of fiber laser and CO 2 laser was performed with respect to the functional properties and cut quality of the cut edge for 6-mm-thick S235JR steel. Characterization of the cut specimens showed high accuracy, low surface roughness value, and good repeatability for both sources.…”
Section: Introductionmentioning
confidence: 99%
“…However, the standard [8] clearly states that the mean height of the profile Rz5 and the value of the perpendicularity tolerance of the surface after cutting "u" are used to qualify the cutting quality. Authors of the paper [9] compared the quality of cutting with a CO 2 laser and a fibre laser based, among others, on the standard [8]. It was demonstrated that greater dimensional quality, better roughness, higher drag (n) quality, and perpendicularity or angularity tolerance (u) were obtained for cutting using a fibre laser.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that fibre laser cutting gives a more accurate surface at the same linear energy consumption of 55.4 kJ/m. According to the authors, a major impediment is the high purchase price of fibre lasers [47]. Zaitsev et al simulated the melting dynamics of inert gas laser cutting.…”
Section: Synthesis Of Literaturementioning
confidence: 99%